Design of Pyrolysis Plant for Waste Methyl Ethyl Ketone from the Polarizer Manufacturing Process - Yan-Quan Zhang; Chih-Hsiang Huang; Chao-Yuan Wu; Yao-Hsuan Tseng (Applied Sciences, 2023)
The rapid growth of the semiconductor industry has made significant strides in addressing clean energy concerns. However, there are still unresolved issues related to waste solvents. One promising approach to tackle these challenges is through pyrolysis. This study selected waste methyl ethyl ketone (MEK) from the industrial sector as the feedstock for pyrolysis, resulting in various residual products such as fixed carbon (char), carbon soot, and fuel gases. Experimental results demonstrated that operating temperatures between 750 and 900 °C under anaerobic conditions yielded 5% to 10 wt% of fixed carbon, along with a small amount of tar and 80% to 90% of fuel gases. The research included lab-scale pilot experiments and field-scale system studies to develop a comprehensive concept for a thermal cracking plant. SolidWorks and Aspen Plus software were applied for calculations involving heat-transfer coefficients, residence time, and the utilization of fuel gases with a boiler or burner. A field system was constructed to scale up the pyrolysis process and effectively eliminate waste solvents, incorporating an automated procedural process.